Design of Shunt Active Filter Based Solar PV System Based on P-Q Theory to Enhance Power Quality (International Journal of Food and Nutritional Sciences, 2021)
There are numerous alternatives, but there is no accepted method for rating the active filters. Basic SAPF principles and theoretical ideas are used to define the filter and circuit design. The PWM filter controller (p-q) is designed using the power theory. The shunt active filters were validated using a Simulink model. According to studies, the grid's electricity quality can be confirmed.